Forestación con Eucalipto y su relación con la Agroindustria en las Zonas Altoandinas, de La Región La Libertad, 2017 - Chilón Amambal, Edgar (2017)
The present work aims to determine the relationship between forestation with eucalyptus and the agroindustry in the high Andean areas of La Libertad Region, 2017. Available information indicates the importance of the forest sector with eucalyptus for the mitigation of change climate through soil conservation, hydrological regulation; protection of biological diversity. In addition, agroindustry can be a significant contributor to soil erosion, through various programs, projects, forestry policies and local agreements that help them to make informed decisions on investments, at different scales of space and time, to development of the community as a stimulating entity of the jobcreating economy and regional growth. On the other hand we can mention that Eucalyptus plantations are suitable to obtain products with industrial yield for the production of cellulose, its wood can be inserted in the market as a competitive alternative of sustainable production and take advantage of its physical-mechanical properties for the traditional use and the alternative.